AOI Rivers for Visualizing Dynamic Eye Gaze Frequencies. (1st July 2013) - Burch, Michael; Kull, Andreas; Weiskopf, Daniel
Abstract: It is difficult to explore and analyze eye gaze trajectories for commonly applied visual task solution strategies because such data shows complex spatio‐temporal structure. In particular, the traditional eye gaze plots of scan paths fail for a large number of study participants since these plots lead to much visual clutter. To address this problem we introduce the AOI Rivers technique as a novel interactive visualization method for investigating time‐varying fixation frequencies, transitions between areas of interest (AOIs), and the sequential order of gaze visits to AOIs in a visual stimulus of an eye tracking experiment. To this end, we extend the ThemeRiver technique by influents, effluents, and transitions similar to the concept of Sankey diagrams. The AOI Rivers visualization is complemented by linked spatial views of the data in the form of heatmaps, gaze plots, or display of the visual stimulus. The usefulness of our technique is demonstrated for gaze trajectory data recorded in a previously conducted eye tracking experiment.